THE NEED FOR ELECTORAL REFORMS IN INDIA AND THEIR IMPLICATIONS - Dr. Sanjay Tiwari (IJRDO - Journal of Social Science and Humanities Research, 2026)
India is the world’s largest democracy, where elections form the core institutional mechanism through which citizens choose their government and hold it accountable. Despite this achievement, the Indian electoral process continues to face serious challenges, including the pervasive influence of money and muscle power, criminalization of politics, vote-buying, biased or opaque media practices, and limited participation of socially marginalized groups. These problems undermine the fairness, transparency, and inclusiveness of elections and erode public trust in democratic institutions. ​This article examines the necessity of electoral reforms in India, outlines the major reforms undertaken so far, and analyzes their broader impact on the quality of democracy. Drawing on constitutional provisions, statutory law, directives of the Election Commission of India, and relevant academic literature, the paper adopts a conceptual and documentary approach to map key reforms such as expenditure limits, measures against criminal candidates, the “one nation, one election” proposal, reforms in political finance, the introduction of Electronic Voting Machines (EVMs), the provision of NOTA (None of the Above), and the expansion of digital and remote voting facilities. ​The analysis shows that reforms promoting cleaner political finance, stronger regulation of criminal candidates, technological innovation in voting, and greater voter awareness can significantly enhance the integrity, inclusiveness, and credibility of elections. At the same time, persistent gaps in enforcement, transparency, and citizen engagement indicate that electoral reform in India must be understood as a continuous, long-term process rather than a one-time intervention. The article argues that coordinated efforts by the state, the Election Commission, political parties, and citizens are essential to ensure that India’s electoral democracy is not only numerically vast but also substantively robust and just.